Decentralization and decision-making among fishery extension workers - Pacete, Ofelia T. (Danyag : Journal of Humanities and Social Sciences, 2003)
In response to the call for increasing the decision-making competencies of fishery extension workers (FEWs), this study assesses the extent and level at which decision-making has been devolved to LGUs by the national headquarters and regional offices. The duties and responsibilities of FEWs are considered, including the problems encountered in performing them with proposed solutions. Specific problem areas in decision-making are identified with accompanying modalities for resolution. Several mechanisms are assessed to facilitate decentralization in decision-making. Finally, highly significant areas for policy recommendations to enhance decentralized decision-making are considered for eventual communication to local officials and other influentials in the fishery industry. In due time, the FEWs can help the coastal people actualize their dreams of a more progressive life ahead.